REAKSI PASAR MODAL TERHADAP PENGUMUMAN PAKET KEBIJAKAN EKONOMI JILID 1, 5, 7, 11 DAN 13 - Adelia Nandira Maharani; Irni Yunita (JRAK, 2018)
The purpose of this research is to analize market reaction to the 1st, 5th, 7th, 11th and 13th economic policy packages. This research uses event study approach. Its measurement of market reaction would be seen from the difference of Abnormal Return and Trading Volume Activity before and after the events. Sample of this research was selected through purposive sampling techniques which include 12 firms. The data analysis used paired sample of t-test. These results indicated that there is no difference in abnormal returns before and after 1st, 5th, 7th and 13th economic policy packages announcement. There is a difference in abnormal returns before and after 11th economic policy packages announcement. There is no difference in trading volume activity before and after 1st, 5th, 7th, 11th and 13th economic policy packages announcement. Market reacts fast and protracted to the event which indicate that market is not efficient in semi strong-form.